Influence of computational parameters on turbulence flow structure characteristic in two dimensional idealized urban street canyon for large eddy simulation / Norharyati Saleh - Saleh, Norharyati (2022)
The use of Computational Fluid Dynamics (CFD) as a research tool has been utilized in many ways to predict the turbulent flow nature in an urban environment such as a street canyon. A review of past relevant studies on the atmospheric process in large or long street canyons indicates an arbitrary selection mainly for two parameters, namely computational domain and grid resolution that have significant influences on the accuracy and reliability of the predicted flow field, particularly for turbulence flow phenomena. However, most of the studies were merely done at the early stage of simulation and most sensitivity tests on those parameters have been done separately in previous studies while the rigorous study on the correlation among the grid resolution size and computational domain size is still limited. This study performs a series of large eddy simulations (LES) to investigate the turbulent flow fields within and above a two dimensional idealized street canyon with a unity aspect ratio (ratio of street width, IV to building height, H),